Parallel texts from the Swedish Crime Victim Compensation and Support Agency - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Parallel texts downloaded from the website of the Swedish Crime Victim Compensation and Support Agency.

Parallel texts downloaded from ageny's website. What was actually downloaded were pdf files. The txt files that are available are the result of running the pdf files through the pdftotext command from an ubuntu shell.

Parallella texter nedladdade från Brottsoffermyndighetens webbplats. Det som nedladdades var egentligen pdf-filer. Parallella texter nedladdade från SIDAs webbplats. Det som nedladdades var egentligen pdf-filer. De txt-filerna som finns tillgängliga är resultat ur en körning av kommandot pdftotext i ubuntu-skal.
Parallella texter från Brottsoffermyndigheten
Keywords: crime victims; brottsoffer; crime and security; brott; Legislation and legal systems; Lagstiftning och rättssystem; Crime and law enforcement; Kriminalitet och rättstillämpning; SOCIAL WELFARE POLICY AND SYSTEMS; SOCIAL VÄLFÄRDSPOLITIK OCH VÄLFÄRDSSYSTEM; Social Sciences; Samhällsvetenskap; Law; Juridik; Languages and Literature; Språk och litteratur